A computational geometric / information theoretic method to invert physics-based MEC models attributes for MEC discrimination - Deschaine, L.M.; Nordin, P.; Pintér, Já.D. (Математичні машини і системи, 2011)
The presence of subsurface munitions and explosives of concern (MEC) is a significant issue worldwide. Discrimination of MEC from non-MEC items enables resources be focused on mitigating risk. Geophysical data is collected and physically-based models inverted with the intent that the inverted model parameters form the basis for MEC discrimination. However, MEC discrimination via model inversion has significant difficulties in noisy environments and with uncertain sensor location. Our computational geometric approach is demonstrated to produce an information-rich set of attributes useful for MEC discrimination including the inverted model information content along with valuable additional information not obtainable using the inversion approach. Наявність залишкових підповерхневих боєприпасів і вибухових речовин (БВР) є серйозною проблемою в усьому світі. Дискримінація БВР від не БВР-елементів дозволяє спрямовувати ресурси на пом'якшення ризиків. Збір фізичних даних і інвертування, моделей, що фізично визначаються, проводяться з наміром використовувати інвертовані модельні параметри як базис для дискримінації БВР. Однак дискримінація БВР через модельну інверсію стикається зі значними труднощами в середовищах з шумами, а також при невизначеному місцезнаходженні сенсорів. Наш обчислювально-геометричний підхід демонструє можливість отримувати безліч інформаційних атрибутів, корисних для БВР-дискримінації, включаючи інформаційний зміст інвертованої моделі разом з цінною додатковою інформацією, недоступною при використанні інверсного підходу. Наличие остаточных подповерхностных боеприпасов и взрывчатых веществ (БВВ) является серьезной проблемой во всем мире. Дискриминация БВВ от не БВВ-элементов позволяет направлять ресурсы на смягчение рисков. Сбор физических данных и инвертирование физически определяемых моделей производятся с намерением использовать инвертированные модельные параметры в качестве базиса для дискриминации БВВ. Однако дискриминация БВВ через модельную инверсию сталкивается со значительными трудностями в средах с шумами, а также при неопределенном местоположении сенсоров. Наш вычислительно-геометрический подход демонстрирует возможность получать множество информационных атрибутов, полезных для БВВ-дискриминации, включая информационное содержание инвертированной модели вместе с ценной дополнительной информацией, недоступной при использовании инверсного подхода.